Efficacy of astragalus in the treatment of radiation-induced lung injury based on traditional Chinese medicine: A systematic review and meta-analysis of 25 RCTs. Issue 36 (9th September 2022) - Pang, Xue-Meng; Cai, Hou-Hao; Zhao, Jie; Sun, Ping-Yi; Shi, Jing-Jing; Zhang, Yan-Li; Liu, Juan; Liu, Zong-Chen; Zheng, Xin
Abstract : Background: Astragalus (Hedysarum Multijugum Maxim., Huangqi) is a Chinese herbal medicine, and according to the theory of traditional Chinese medicine (TCM), Chinese medicinal preparations containing astragalus can be used clinically to treat radiation-induced lung injury (RILI). To systematically review the efficacy and safety of Chinese medicinal preparations containing astragalus in the prevention and treatment of RILI by means of meta-analysis. Methods: A systematic literature on randomized controlled trials (RCTs) of prescriptions containing astragalus in the treatment of RILI by Pubmed, Embase, Web of Science, Cochrane Library, China Biomedical Literature Database, China National Knowledge Infrastructure, China Science and Technology Journal Database, WANFANG Database. The retrieval time is from the establishment of the database to January 18, 2022. Meta-analysis, heterogeneity test and sensitivity analysis were performed on eligible RCTs using Revman 5.4 software and STATA 17.0 software, and a "funnel plot" was used to analyze potential publication bias. Results: A total of 25 RCTs were included, including 1762 patients, and the most widely used drugs were heat-clearing and detoxifying, yin-nourishing and qi-nourishing. The prescriptions containing astragalus can significantly reduce the total incidence of RILI ( P < .01), improve the total effective rate and cure rate of RILI ( P < .01), improve the quality of life of patients, alleviate breathing difficulties and reduce the expression of inflammatory factors ( P < .01), and no adverse reactions related to TCM treatment were reported. Conclusion: The traditional Chinese medicinal preparation containing astragalus can effectively alleviate the clinical symptoms of RILI, reduce the toxic side effects, and is safe to use in clinic.